Using the Technology of Blended Learning “Flipped Classroom” in the Formation of Leadership Qualities in Future IT Specialists - Io. L. Zagoumennov (Открытое образование (Москва), 2023)
The purpose of the work is to substantiate a practice-oriented interactive information and pedagogical technology of blended learning “flipped classroom” in the formation of leadership qualities in future IT specialists. The relevance of this problem is due to the process of transition of the national economy to an innovative development path and the demand in this regard for IT specialists who are ready to become leaders in their field and are able to captivate and lead their teams.Materials and methods. To achieve this goal, methods of comparative analysis of existing domestic and foreign approaches to the use of blended learning technology “flipped classroom” were used, as well as a general scientific system approach that allows to study the process of interaction between subjects and objects of educational activity at a university and the possibility of increasing the efficiency of the educational process based on the use of digital tools and distance learning system (DLS) Moodle. The developed technology was tested in the Minsk branch of the Plekhanov Russian University of Economics in work with students of the direction of training 38.03.05 “Business Informatics”, the profile of the program is “Digital Transformation of Business”.Results. In the framework of the study, a practice-oriented interactive information and pedagogical technology of blended learning “flipped classroom” was developed and successfully tested, aimed at developing leadership qualities in future IT specialists. The proposed use of blended learning technology successfully responds to the challenges that foreign and domestic researchers and practitioners face when implementing the flipped classroom technology, namely: students’ commitment to the traditional passive learning format, their lack of motivation necessary for independent work and cooperation with each other in the process of preparing for the classroom and, as a result, the unpreparedness of students for the classroom and the low level of their activity and cooperation in the classroom.Conclusion. The proposed information and pedagogical technology makes it possible to develop a corporate team culture in student groups and forms their ability to lead their teams to success in educational, research and innovation activities.